Hepatic fibrosis and cirrhosis in the Fontan circulation: a detailed morphological study. Issue 4 (26th October 2007) - Kendall, T J; Stedman, B; Hacking, N; Haw, M; Vettukattill, J J; Salmon, A P; Cope, R; Sheron, N; Millward-Sadler, H; Veldtman, G R; Iredale, J P
Abstract : Aims: To describe the histological features of the liver in patients with a Fontan circulation. Methods: Specimens from liver biopsies carried out as part of preoperative assessment prior to extracardiac cavopulmonary conversion of an older style Fontan were examined and scored semi-quantitatively for pertinent histological features. To support the use of the scoring, biopsy specimens were also ranked by eye for severity to allow correlation with assigned scores. Results: Liver biopsy specimens from 18 patients with a Fontan circulation were assessed. All specimens showed sinusoidal fibrosis. In 17 cases there was at least fibrous spur formation, with 14 showing bridging fibrosis and 2 showing frank cirrhosis. In 17 cases at least some of the dense or sinusoidal fibrosis was orcein positive, although a larger proportion of the dense fibrous bands were orcein positive compared with the sinusoidal component. All specimens showed marked sinusoidal dilatation, and 14 showed bile ductular proliferation; 1 showed minimal iron deposition, and 1 showed mild lobular lymphocytic inflammation. There was no cholestasis or evidence of hepatocellular damage. Similar appearances were observed in 2 patients with severe tricuspid regurgitation. Discussion: The histological features of the liver in patients with a Fontan circulation are similar to those described in cardiac sclerosis. Sinusoidal dilatation and sinusoidal fibrosis are marked in the Fontan series. The presence of a significant amount of orcein negative sinusoidal fibrosis suggests there may be a remediable component, although the dense fibrous bands are predominantly orcein positive, suggesting chronicity and permanence. No inflammation or hepatocellular damage is evident, suggesting that fibrosis may be mediated by a non-inflammatory mechanism.